Trends and standards in software selection in Nigerian libraries (2002)
TINLIB(now t series) is the most popular library automation package in Nigeria but many academic libraries are at the verge of migrating to other systems. The decision to adopt one of the numerous library packages is still a difficult one. The advent of library software, the trends in the country and across the African scene were discussed while the steps to responsible software selection were highlighted. The features of a good library software were also discussed in details. The scenario of library software use in Nigeria and the challenges were explored. The pricing of library software products and other considerations such as technical support and vendor issues were featured. Recommendations towards successful selection and utilization of library software in Nigeria were made. A comparative study of five common library software packages in Africa was also made so as to assist libraries in Nigeria that may want to select a library package for use. The need for Nigerian academic libraries to pull together as evident in other African countries was emphasized as well the need for involvement of professional bodies in setting standards in library software products